2003
DOI: 10.1016/s0749-596x(03)00026-3
|View full text |Cite
|
Sign up to set email alerts
|

Charting the time-course of VP-ellipsis sentence comprehension: Evidence for an initial and independent structural analysis

Abstract: We exploited the properties of VP-ellipsis constructions containing inherently reflexive and inalienable possession verbs that severely constrained final interpretation (e.g., "The policeman perjured himself, and the fireman did too…"). Using the cross-modal lexical priming task, we found that listeners reactivated the subject NP from the first clause at the elided position in the second clause (i.e., the "strict" reading), even though verb properties disallowed such an interpretation. We also found that liste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
38
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 39 publications
7
38
1
Order By: Relevance
“…If this were the case, then we would have observed reactivation of the subject not only after unaccusative verbs but also after unergative verbs; but we did not. Indeed, CMLP studies examining reactivation have predominantly found such effects only for those NPs that have been displaced or copied from their base-generated positions (e.g., Shapiro et al 2003).7…”
Section: For Discussion)mentioning
confidence: 99%
“…If this were the case, then we would have observed reactivation of the subject not only after unaccusative verbs but also after unergative verbs; but we did not. Indeed, CMLP studies examining reactivation have predominantly found such effects only for those NPs that have been displaced or copied from their base-generated positions (e.g., Shapiro et al 2003).7…”
Section: For Discussion)mentioning
confidence: 99%
“…This is critical because it has been shown that allowing participants to pace themselves slows down processing (Rayner 1998); such slowed processing follows from conscious reflection, which in turn allows any number of constraints to permeate the processing system. Furthermore, there is a reasonable set of evidence using tasks such as cross-modal priming that suggests that lexical constraints do not affect initial syntactic analysis (Swinney and Osterhout 1990;Shapiro et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Murphy (1985) varied the distance between the ellipsis and its antecedent, along with the length of the antecedent and the syntactic parallelism of the antecedent in both surface and deep anaphors (VP ellipsis versus ''do it'' anaphora; see Sag, 1976;Shapiro, Hestvik, Lesan, & Garcia, 2003). A longer distance between the antecedent and ellipsis slowed reading times, as did increasing the length of the antecedent.…”
Section: Methodsmentioning
confidence: 99%